Ministry of Woman, Family & Community Development / Muhammad Shahrin Safri ... [et al.] - Safri, Muhammad Shahrin; Abd Suki, Muhammad Hazim; Ruzaidi, Rais Adlan; Ismail, Nazrul Ikwan; Mohamad, Muhammad Zulhilmi (2013)
Building of the Ministry of Women, Family and Community Development (KPWKM) is a government building which is located at Precinct 4, 62100 Putrajaya, Malaysia. The code for this building is 4G11. Mean of 4G11 is 4 stand for the location of the building at Precinct 4, G stand for Government Building and 11 is stand for this building is 11st building at precinct 4. This building is one of the tallest buildings at Putrajaya. This building has 45 floor level and 3 basement area provide for car park. The building located at the side of KPWKM building is Building of Ministry of Housing & Local Government. Both of the buildings are sharing same basement. Ministry of Women, Family and Community Development building is one of the buildings that used system which is advanced in technology such as Building Automation System (BAS), Alarm & Security System and Fire Fighting System. In additional, in this building have four departments which is related to the Ministry of Women, Family and Community Development (KPWKM). The departments are Department of Women Development (JPW), Department of Social Welfare Malaysia (JKMM), The National Population and Family Development Board (NPFDB), Social Institute of Malaysia (ISM).